Biological Flora of the British Isles: Quercus rubra. (20th April 2020) - Dyderski, Marcin K.; Chmura, Damian; Dylewski, Łukasz; Horodecki, Paweł; Jagodziński, Andrzej M.; Pietras, Marcin; Robakowski, Piotr; Woziwoda, Beata
Abstract: This account presents information on all aspects of the biology of Quercus rubra L. (Red Oak, Northern Red Oak; syn. Q. boreali s, Q. maxima ) that are relevant to understanding its ecological characteristics and behaviour. The main topics are presented within the standard framework of the Biological Flora of the British Isles: distribution; habitat; communities; responses to biotic factors; responses to environment; structure and physiology; phenology; floral and seed characters; herbivores and disease; history; and conservation. Quercus rubra is a large deciduous tree native to eastern North America. In its native range this species is one of the most important mid‐successional tree species. Since the 18th century Q. rubra has been introduced into forest management in Europe and elsewhere. Currently, Q. rubra is a naturalized species in 23 countries. It is an important source of wood, and this was one of the most important reasons for its introduction in forests. In forest management this species is valued for its high growth rate and drought resistance. Red Oak is also widely cultivated in Europe for its ornamental value—red leaves in autumn and smooth, grey bark. Red Oak is a threat to native species within its introduced range as it can alter environmental conditions beneath its canopy, especially by decreasing light availability and litter decomposition rate. Such conditions also contribute to biotic homogenization of the understorey vegetation. Q. rubra is widely dispersed by small mammals and birds, up to 1, 500 m from seed sources, thereby increasing its potential invasiveness. In Europe Q. rubra seems to be less prone to herbivores and fungi, in contrast to its native range, where it is grazed by ungulates and insects, and infected by Phytophthora and oak wilt. Due to its higher tolerance to drought than native European oaks, Q. rubra is claimed to be one of the species replacing native trees which are decreasing due to climate warming. However, consideration of all possible consequences is needed in wide‐scale introduction of alien species, such as Q. rubra, due to negative impacts on native ecosystems. Abstract : Quercus rubra (Red Oak) was introduced from North America into Europe around the beginning of the 17th century, mainly for its ornamental value and timber production. Now this oak tree is very popular and claimed to be a useful alternative to native species, despite its invasiveness. However, we still do not know how much of its invasiveness is connected with wide introductions or with biological traits. Nevertheless, it is frequent and distinctive, because of its large leaves that colour spectacularly red‐brown in the autumn. It is even depicted on a Polish coin of low denomination.